Reversible cryopreservation of living cells using an electron microscopy cryo-fixation method - Hübinger, Jan; Han, Hong-Mei; Grabenbauer, Markus (PLOS ONE, 2016)
Rapid cooling of aqueous solutions is a useful approach for two important biological applications: (I) cryopreservation of cells and tissues for long-term storage, and (II) cryofixation for ultrastructural investigations by electron and cryo-electron microscopy. Usually, both approaches are very different in methodology. Here we show that a novel, fast and easy to use cryofixation technique called self-pressurized rapid freezing (SPRF) is-after some adaptations-also a useful and versatile technique for cryopreservation. Sealed metal tubes with high thermal diffusivity containing the samples are plunged into liquid cryogen. Internal pressure builds up reducing ice crystal formation and therefore supporting reversible cryopreservation through vitrification of cells. After rapid rewarming of pressurized samples, viability rates of > 90% can be reached, comparable to best-performing of the established rapid cooling devices tested. In addition, the small SPRF tubes allow for space-saving sample storage and the sealed containers prevent contamination from or into the cryogen during freezing, storage, or thawing.